Examining interactive whiteboard-based instruction on the academic self-efficacy, academic press and achievement of college students*. (4th May 2018) - Shi, Yinghui; Peng, Changling; Yang, Harrison Hao; MacLeod, Jason
Abstract: The study reported here examined college students' academic self-efficacy, 'academic press' and learning achievement, as well as the association between these three variables within learning contexts using interactive whiteboard-based instruction. A quasi-experimental study was conducted using a sample ( n  = 103) of first-year college students in China. Participants were taught English by either an interactive whiteboard-based or traditional lecture-based instructional approach for three months. The results showed that the interactive whiteboard-based instructional intervention cultivated higher levels of academic press and academic self-efficacy among students and a significant, positive correlation was identified between these two variables. Students' learning achievement was not affected by the instructional intervention. These results indicate that interactive whiteboard-based instruction offers some distinct benefits. In future work, additional research is needed to clarify how the instructional model relates to understanding learning achievement.